2013
DOI: 10.1097/jsm.0b013e31825b6995
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of the Acromiohumeral Distance in Elite and Recreational Female Overhead Athletes

Abstract: The AHD is larger on the dominant side compared with the nondominant side and in elite female athletes compared with recreational female athletes. Moreover, less reduction of the AHD occurs in the elite athlete group during the first 45 degrees of abduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
(40 reference statements)
0
19
1
Order By: Relevance
“…Since study methods were similar across the ultrasound studies, forest plots were constructed to illustrate the range of ICC values reported (figures 3 and 4). The SE of measurement values for AHD were more variable; they were below 1 mm in the high quality studies by Duerr24 and Seitz et al 31 and in a number of lower quality studies;26 28 29 however, Kalra et al 25 reported higher SEM values of 0.9–1.6 mm in their high quality study. Three studies reported the minimal detectable change (MDC) for AHD measurement, which is an important concept representing the amount of change required to exceed measurement variability.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Since study methods were similar across the ultrasound studies, forest plots were constructed to illustrate the range of ICC values reported (figures 3 and 4). The SE of measurement values for AHD were more variable; they were below 1 mm in the high quality studies by Duerr24 and Seitz et al 31 and in a number of lower quality studies;26 28 29 however, Kalra et al 25 reported higher SEM values of 0.9–1.6 mm in their high quality study. Three studies reported the minimal detectable change (MDC) for AHD measurement, which is an important concept representing the amount of change required to exceed measurement variability.…”
Section: Resultsmentioning
confidence: 84%
“…There were varied time intervals used for the repeated scans, ranging from within-session scans to others taken up to 2 weeks26 or 6 weeks later 29. While various factors may influence the normal variation in AHD over time (such as posture, fatigue, activity), no studies described controlling for these factors.…”
Section: Resultsmentioning
confidence: 99%
“…For example, excellent intra-rater reliability (0.87-0.94) and moderate-toexcellent inter-rater reliability (0.64-0.92) of the AHD have been demonstrated using ultrasound in ablebodied individuals with healthy and impinged shoulders. 9,17,20,21 Moderate intra-and inter-observer reliability using unmarked sonograms has also been reported. 17 Discriminant validity of the AHD between affected and unaffected shoulders was determined in a hemiplegic population.…”
Section: Introductionmentioning
confidence: 99%
“…22 Maenhout et al reported similar AHD reduction in 29 elite athletes and 33 recreational athletes using sonographic elevation during the first 45°active shoulder abduction. 21 However, no information was provided on the actual AHD at 90°of abduction in these populations. Our findings are also consistent with a previous MRI study that found the co-contraction imbalance between deltoids and shoulder depressors was most prominent around 90°abduction, resulting in a narrower Figure 4 Bland-Altman plot of average rater 1 and 2 of the AHD measurement in MWUs with SCI (A) and able-bodied (B).…”
Section: Effects Of Shoulder Positioningmentioning
confidence: 99%
See 1 more Smart Citation